2008
DOI: 10.1002/macp.200800161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crosslinking Methods on Structure and Properties of Cellulose/PVA Hydrogels

Abstract: A series of hydrogels were prepared from cellulose and PVA in NaOH/urea aqueous solution using both physical and chemical crosslinking methods. The hydrogels were secure and biodegradable materials. Their structure and properties were characterized by FTIR spectroscopy, DSC, XRD and SEM. The results indicated that all of the cellulose/PVA hydrogels exhibited homogeneous porous structures and a certain miscibility. The swelling degree and water uptake of the chemical hydrogels were markedly higher than those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(120 citation statements)
references
References 32 publications
4
115
1
Order By: Relevance
“…[103] Several groups have also explored freeze/thaw cycling-a process whereby hydrogel precursor materials are sequentially frozen-to induce strong physical crosslinking and enhance the mechanical properties of structured hydrogels. [105][106][107] When the number of freeze/thaw cycles is increased, the hydrogel components pack tighter to form a stronger, stiffer network. However, it must be noted that the porosity is also decreased upon increased cycling via the same mechanism, [105] limiting the practical utility of freeze/thaw processes for producing large pore volume materials.…”
Section: High-strength Hydrogelsmentioning
confidence: 99%
“…[103] Several groups have also explored freeze/thaw cycling-a process whereby hydrogel precursor materials are sequentially frozen-to induce strong physical crosslinking and enhance the mechanical properties of structured hydrogels. [105][106][107] When the number of freeze/thaw cycles is increased, the hydrogel components pack tighter to form a stronger, stiffer network. However, it must be noted that the porosity is also decreased upon increased cycling via the same mechanism, [105] limiting the practical utility of freeze/thaw processes for producing large pore volume materials.…”
Section: High-strength Hydrogelsmentioning
confidence: 99%
“…The swelling measurements were carried out following the methodology reported by Chang et al [40]. To reach swelling equilibrium, PVA and PVA/BC biomaterials were hydrated in distilled water for over 2 weeks at room temperature.…”
Section: Swelling the Swelling Ratio Of Biomaterials Is Relevant In Cmentioning
confidence: 99%
“…"Review of cellulosic absorbents," BioResources 8(4), 6556-6629. 6565 Gürdağ et al 2001;Kim & Mun 2009;Feng et al 2010a;Bao et al 2011;Pourjavadi et al 2009 Divinylsulfone (DVS) Lionetto et al 2003;Sannino et al 2004a Vitta et al 1986;Askari et al 1993 Epichlorohydrin (ECH) Chang et al 2008Chang et al , 2009a2010 1,2,3,4-butanetetracarboxylic dianhydride (BCTA) Kono & Fujita 2012; Diallyltartardiamide (DATDA) Pohjanlehto et al 2011 Glutaraldehyde (GA) Shang et al 2008;Zamani et al 2010 Polyelectrolyte complexes A unique type of hydrogel can be formed through the use of pairs of oppositely charged polyelectrolytes via the formation of polyelectrolyte complexes (PECs). At least one of the polyelectrolytes could be a cellulosic material such as carboxymethyl cellulose (CMC) (Feng et al 2006;Feng and Pelton 2007) or hemicellulose (Salam et al 2011b).…”
Section: Interpenetratingmentioning
confidence: 99%
“…As one means to control this balance, Lionetto et al (2005) showed that the degree of crosslinking can be monitored during the process by evaluation of ultrasonic wave propagation. Chang et al (2008) showed that the type of crosslinking, i.e. covalent-type vs. physical crosslinking, also can make a big difference relative to results.…”
Section: Crosslinkingmentioning
confidence: 99%
See 1 more Smart Citation